Pengaruh Tekhnik Drama Voice Terhadap Penguasaan Pronunciation Pada Mahasiswa Semester Satu Pendidikan Bahasa Inggris Universitas Mathla’ul Anwar Banten Tahun Akademik 2019/2020 - Rizdki Elang Gumelar; Riandi Riandi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
The purpose of this study is to investigate the the influence of drama voice techniques towards students’ pronunciation mastery in the first grade students of English Education Faculty at University of Mathla’ul Anwar Banten academic years 2019/2020 which was located on Jl. Raya Labuan KM. 23, Saketi, Pandeglang, Banten, Indonesia 42273. The population of this study was 10 students and the sample was 10 students. This study is carried out to find out whether there is a significant influence of drama voice techniques towards students’ pronunciation mastery. This research used a quantitative true experimental approach using Pretest-Posttest Control Group Design. In this research there are two variables, they are independent variable and dependent variable. The independent variable is Drama Voice Technique (X), and then the dependent variable is Pronunciation Mastery (Y). In collecting the data, the instrument used in this research is test. The form of the test is oral and written (multiple choice) test. The hypothesis analysis used analysis of t-test. In analysing the hypothesis this research used SPSS statistics 22. Finding of this study showed that a significant influence of drama voice techniques towards students’ pronunciation mastery. It could be seen that signification value (p-value) = 0.003 < α = 0.05, so H1 is accepted and H0 is rejected. On the other word, there is a significant influence of drama voice techniques towards students’ pronunciation mastery. Based on the result above, the researcher concluded that pronunciation is one of the elements in English. Teaching English using Drama Voice technique gave positive contribution especially on improving Pronunciation mastery